การพัฒนาโปรแกรมการให้ความรู้ผู้ปกครอง เรื่องการป้องกันปัญหายาเสพติดในเด็ก - นรเศรษฐ์ ศรีแก้วกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
The purpose of this research was to develop the parent education program on drug prevention of young children. The subjects were 25 parents of young children in Doon community, Srisaket Province. The study comprised of 4 steps, namely, 1) studying baseline data, 2) constructing program for parent education on drug prevention of young children, 3) testing the program, and 4) modifying the program. The research instruments were knowledge test, an opinion questionnaire on drug preventative for child rearing and a questionnaire of opinion in program participation. Data were analyzed by mean, standard deviation, and t-test. The results were summarized as follows: 1. After using the program, the parents had higher drug knowledge scores than before and the scores were higher than 75% at the .01 level of significance. 2. After using the program, the parents had higher opinion scores in drug prevention child rearing than before and the scores were higher than 80% at the .01 level of significance. 3. Most parents opinion concerning the participation of the program on the satisfaction of instruction, the presentation of cd-rom and tape, the appropriateness of parent handbook, place, and the usefulness of participation in the program were high. 4. The complete program consisted of principles, objectives, content, qualification of users, documents and instrument, steps of instruction, and program evaluation.